Endometriosis among African women - Ezekiel O Mecha; Joseph N Njagi; Roselydiah N Makunja; Charles O A Omwandho; Philippa T K Saunders; Andrew W Horne (Bioscientifica, 2022)
Endometriosis has long been wrongly perceived to be rare among women of African descent. The misconception about the prevalence of endometriosis among African women has significantly contributed to long diagnostic delays, limited access to diagnosis and care, and a scarcity of research on the condition among African women. In this commentary, we highlight the prevalence of endometriosis among African women, the state of endometriosis care in Africa, and the gaps in knowledge that need to be addressed. Based on the available data, the prevalence of endometriosis in Africa is likely higher than previously thought, with varying subtypes. There is a long diagnostic delay of endometriosis among African women. Additionally, endometriosis care in Africa from the general population and health practitioners is poor; this can be attributed to the high diagnostic cost, scarcity of trained specialists, as well as patients' inability to express their symptoms due to societal taboos surrounding menstrual health. Public sensitization on endometriosis may help improve endometriosis diagnosis and care in Africa.